(untitled) (Research, Society and Development, 2021)
Autistic Spectrum Disorder is a neurodevelopmental disorder that begins to present itself before the age of three. It is also classified as behavioral syndrome that gives rise to a wide variety of clinical symptoms. Autism is not a single disease, but a complex developmental disorder, defined from a behavioral perspective, with multiple causes and varying degrees of severity. Medication is an option to reduce a large number of bad behaviors. When core symptoms cripple the individual’s development and prevent the effects of other therapies such as education and behavioral therapy, medications for specific symptoms should be used. In recent decades, the prevalence of people diagnosed with autism has increased, indicating the need for public policies that meet the needs of patients and their families. In this context, the pharmacist plays an important role, mainly in the guidelines related to the drugs used in the treatment.